Recommended earthquake Loading Model for Peninsular Malaysia - Looi, T.W., Engr.; Hee, M.C., Ir.; Tsang, H.H., Dr.; Lam, N.T.K., Dr. (The Institution of Engineers, Malaysia, 2013)
Link to publisher’s homepage at http://www.myiem.org